Biodiesel Production from a Naturally Grown Green Algae Spirogyra Using Heterogeneous Catalyst: An Approach to RSM Optimization Technique - Teku Kalyani; Lankapalli Sathya Vara Prasad; Aditya Kolakoti (International Journal of Renewable Energy Development, 2023)
The present study focuses on oil extraction and biodiesel production from naturally grown green Spirogyra algae. Solvent oil extraction and oil expeller techniques were used to extract the Spirogyra algae oil (SALO), and the oil yields were compared to identify the most productive method. Using chicken eggshell waste (CESW) heterogeneous catalyst (HC) was prepared for the production of Spirogyra algae oil biodiesel (SALOBD). Furthermore, Box–Behnken (BB) assisted response surface method (RSM), an optimisation technique, was used in this study to achieve maximum algae biodiesel yield. From the 29 experimental trails, 96.18 % SALOBD was achieved at molar ratio (10:1), heterogeneous catalyst (0.6 wt.%), temperature (48 oC), and time (180 minutes). The predicted values of R2 (97.51%) and Adj. R2 (95.02 %) is found to be encouraging and fits well with the experimental values. The output results show that HC was identified as the significant process constraint followed by the time. The fatty acid composition (FAC) analysis by Gas Chromatography (GCMS) reveals the presence of 29.3 % unsaturated composition and 68.39 wt. % of the saturated composition. Finally, the important fuel properties of SALOBD were identified in accordance with ASTM D6751. The results obtained using chicken eggshell waste (CESW) for the production of biodiesel were recommended as a diesel fuel replacement to resist energy and environmental calamities.